Implementasi Model PAIKEM terhadap Fokus Belajar Peserta Didik dalam Pembelajaran Bahasa Indonesia - Dhea Santika; Natasya Ariani Ramli; Adrias Adrias; Nur Azmi Alwi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Learning Indonesian requires strong focus from students to achieve a deep understanding and good mastery of the material. One approach that can increase students' focus is by implementing the Active, Innovative, Creative, Effective and Fun Learning Model (PAIKEM). This model emphasizes active interaction between teachers and students, the use of innovative methods, and a creative and fun learning atmosphere. This research emphasizes how the use of the PAIKEM Model can stimulate students' active participation, increase involvement in the learning process, and strengthen understanding and use of Indonesian. Therefore, it is hoped that this research can be an effective means of increasing students' focus in learning Indonesian, paving the way for achieving better and more sustainable learning outcomes.